THE IMPACT OF MINING INDUCED URBANIZATION: A CASE STUDY OF KATHU IN SOUTH AFRICA - Fidelis EMUZE; Cornel HAUPTFLEISCH (Journal of Construction Project Management and Innovation)
Rapidity in urbanization has continued in the past decade despite the realisation that resources are finite. Commerce, migration, employment, industry configuration and population increases are factors that contribute significantly to the urbanization phenomenon. With respect to the contributions of commerce, mining activities have led to the advancement and regression of cities. An abundance of literature exists on the negative effects of urbanization and mining on the environment. The main reason for the research that produced this initial findings was to determine how urbanization, when induced by mining, impacts on the environment and how to ensure future sustainable urbanization. The research was done qualitatively through interviews of knowledgeable individuals within the relevant industries within the mining town of Kathu, in the Northern Cape of South Africa. The research found that centralization of employment, resources and trade lead to urbanization, which is primary driven by the mining industry. In addition, it was observed that mining as a factor that accelerates urbanization, also impact negatively on the environment. Thus, there is a need for a rethink about mining induced urbanisation so as to reduce pollution and other adverse event of secondary activities that support the primary industry of mining.